Comparison study of vitamin c content in various brands of calamansi syrup from Bengkulu City using UV-Vis Spectrophotometry - Mauliani Dwi Nathasyah; Putri Mulia; Samwilson Slamet; Tri Danang Kurniawan; Tika Hardini (Indonesian Journal of Health Science, 2026)
Calamansi oranges are a good source of vitamin C with high content of 27.43/100 g. Calamansi oranges are commonly processed into calamansi syrup. Calamansi syrup is one of flagship products of Bengkulu City, but information regarding the vitamin C content is not listed on the product packaging. This study aims to compare the vitamin C content of calamansi syrup from various brands in Bengkulu City using UV-Vis spectrophotometry. The study involves five samples of calamansi syrup from different brands. Qualitative analysis was conducted using 0.1% KMnO4, Iodine, and FeSO4 reagents, which showed that all five samples tested positive for containing vitamin C. The determination of the maximum wavelength was done at 265 nm with the regression equation y = 0.0659x + 0.0631 and R2 value of 0.9923. The vitamin C content obtained was 1.681% for Sample A, 5.880% for Sample B, 2.342% for Sample C, 1.979% for Sample D, and 2.478% for Sample E. The Kruskal-Wallis statistical analysis showed a significant difference among the samples (p < 0.05), indicating that the vitamin C content varies among the different brands. In conclusion, the five brands of calamansi syrup available in Bengkulu City contain vitamin C with varying levels.